Public service corporate culture development: main problems and trends - Olga V. Rogach, Elena V. Frolova, Tatyana M. Ryabova; Bondaletova, Natalia F.; Liubkina, Nataliia A. (Opción, 2020)
In this article, they analyze the main stages of public service corporate culture development in Russian Federation: the determination of the mission and basic values; the development of traditions and corporate identity; the determination of employee behavior standards; the improvement of the favorable social-psychological climate. The main problem of public service corporate culture development in modern Russian conditions is the contradiction between its declared content and the internal values of its employees. The analysis of public service corporate culture state in Russia showed a regular tendency: the higher the level of management, the stronger the corporate culture.